Hubungan Bermain Pump It Up (PIU) Dengan Kelincahan Tungkai Pada Remaja - Hardini, Kurniani Fatma, Wahyuni, S.Fis.,Ftr.,M.Kes, Totok Budi Santoso, S.Fis.,Ftr.,MPH (2015)
Game of Pump It Up ( PIU) represent the game which orientation to increase achievement besides useful also to eliminate the momentary saturation. Requirement to conducted the body movement can be fufilled in game PIU, One of them is agility at leg, Player have to used the movement which focussed the activity of member move under though at member move also moved. The happening make-up of strength of muscle leg will cause the happening of makeup stability leg. Objective to know the relationship between playing at Pump It Up ( PIU) with the mobility leg at adolescent. Method research type is observational with the approach of cross sectional. Population in this research is 50 responde nt divided to become two group that is 35 responder as a group control and 15 treatment group. Technique analyse the data use the test of normalitas shapiro wilk and test the hypothesis with the correlation of Spearman Rho. Result showed there is relationship play at the Pump It Up ( PIU) with the adolescent agility leg examinee with the correlation of Spearman Rho Test is p value 0,0001. Tabulation test traverse to show the game PIU of during 2,0 - 2,5 month agility have of result with the category excellent 6,7%, good 60% and average 20%. While player PIU of during > 2,6 month agility have of result with the category excellent 13,3%. Conclusion showed there is relationship of game Pump It Up ( PIU) can improve the agility leg at adolescent.